Contemporary Nursing as a Dynamic Response to Evolving Health Challenges - Yusuf, Saldy (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
The concepts of nurse and nursing are inherently interwoven, representing distinct yet inseparable dimensions that are unified by the universal principle of caring. Caring for humanity must be delivered through a holistic approach, wherein therapeutic communication emerges as a defining characteristic of nursing practice. This form of communication serves not only as a therapeutic intervention in fostering interpersonal relationships with patients but also as a vital bridge in collaboration with other healthcare professionals. Within this framework, nurses are ethically and professionally obligated to provide care that is both evidence-based and holistic, while upholding the principles of responsibility and accountability in every intervention they deliver.